Scientific basis for predicting the spread of pests - Fedorenko, A.; Borzykh, O.; Fedorenko, V.; Chaika, V.; Yushchenko, L. (Quarantine and plant protection, 2025)
Goal. To analyze the existing theories of mass reproduction of insects, to evaluate and test the established and newest methods of monitoring and prospects for their use in modern conditions of pest spread. Methods. Entomological, herbological, meteorological and other monitoring, including information technologies: remote sensing, modeling of insect distribution based on GIS analysis of climatic factors. Results. The deterioration of the phytosanitary condition of crops in Ukraine, which has been recorded over the past decade, has occurred as a result of the withdrawal of large areas of arable land from cultivation, global climate warming, increased solar activity and unpredictable successions, mainly of anthropogenic nature. The combination of these factors creates favorable conditions for the mass reproduction and spread of pests, and the penetration of quarantine pests into agricultural lands (in particular, the quarantine pest marble bug (Halyomorpha halys Stål) entered Ukraine from the temporarily occupied Crimea from the Krasnodar region of Russia). The average long-term indicators of the number and distribution of pests in Ukraine have increased, as evidenced by long-term monitoring of the dynamics of the phytosanitary state of agrobiocenoses. Conclusions. The concept of organizing a monitoring and forecasting system and further development of scientific support in plant protection in modern realities based on the following principles is substantiated: modern information technologies; efficiency; real-time connection «monitoring — forecast — consumer»; evolutionary nature, potential for further improvement. In order to green plant protection, increase the efficiency and reliability of forecasting, programs for predicting potential crop losses from a complex of harmful insects have been developed, and the ecological and economic feasibility of chemical crop protection in the current phytosanitary situation has been substantiated.